Aspectos de discricionariedade do gestor público nos casos de dispensa de licitação na lei Nº 14.133/2021 - Geronasso, Vinicius Saldanha (2024)
The evidence-based research seeks a detailed analysis of the discretion of public managers in cases of bidding exemptions, considering the advent of Law No. 14,133/2021. The repeal of previous laws on the subject has created a new scenario for bidding criteria and direct contracting possibilities, justifying the importance of an investigation in this context. The theoretical foundation of the research is substantiated by the theoretical framework and the practical perspective of public management. The qualitative approach is appropriate for understanding the complexity and nuances involved in the decision-making of public managers, while documentary research provides a solid foundation for analysis, considering relevant legislation, regulations, and normative instructions. By considering both the theoretical framework and the practical perspective, this study provides greater clarity on the options available regarding the discretion of public managers in the scope of bidding exemptions